Using Life Cycle Assessment to Evaluate Green and Grey Combined Sewer Overflow Control Strategies - Maria R. C. De Sousa; Franco A. Montalto; Sabrina Spatari (Journal of Industrial Ecology, 2012)
Summary Decentralized approaches to managing urban stormwater are gaining increased attention within the contexts of urban sustainability, climate change adaptation, and as a means of reducing combined sewer overflows (CSOs). This study applied a life cycle assessment (LCA) to comparing the environmental efficiency of three means of equivalently reducing CSOs to the Bronx River (Bronx, NY, USA). Strategy 1 featured decentralized green infrastructure technologies, while “grey” strategies 2 and 3 detained, and detained and treated, respectively, excess flows at the end of pipe. We estimated greenhouse gas emissions (in metric tons of carbon dioxide equivalents [t CO 2 ‐eq]) over the construction, operation, and maintenance phases, including energy consumed at the wastewater treatment plant (WWTP), carbon sequestered, and shading provided by vegetation (in the case of the green approach) over a 50‐year analysis period. The study area comprised the entire drainage area contributing to New York State permitted CSO discharge points associated with the Hunts Point WWTP. The analysis was performed using a hybrid of process and economic input‐output (EIO) LCA methods. The decentralized green strategy outperformed the two grey strategies in terms of this set of environmental metrics. The net emissions of the green strategy over 50 years was 19,000 t CO 2 ‐eq, whereas the grey strategies emitted 85,000 t CO 2 ‐eq (detention) and 400,000 t CO 2 ‐eq (detention and treatment). These results were significantly influenced by the emissions associated with the operation and maintenance activities required for strategies 2 and 3, and the carbon sequestered and shading provided by the vegetation in strategy 1, and suggest that watershed managers who seek to reduce CSOs and reduce carbon footprints would opt for the green approach.